Ophthalmological Disorders In Patients With Giant Inactive Pituitary Adenomas - Urmanova Yulduz Makhkamovna (Genius Journals, 2026)
A total of 68 patients with giant inactive pituitary adenomas (43 men and 25 women) were examined. The average age of the men was 37.12 years, while the average age of the women was 38.15 years. The duration of the disease ranged from 2 months to 25 years. The most common tumor growth among patients was endo-suprasellar - 28(41.1%).observations.The most pronounced visual field disturbances in the form of amaurosis and bitemporal hemianopsia were observed in patients with endo-suprasellar growth – amaurosis(10.7%), bitemporal hemianopsia(89.3%), as well as in the case of a total growth variant – amaurosis(23%), bitemporal hemianopsia(79.9%)The most pronounced neurological disorders in the form ofdiencephalic-stem disorders (pyramidal symptoms, decreased reflexes and diffuse muscle tone) were observed in patients with a total growth variant, with retrosellar growth and with invasion into the brain
Keywords: Giant; inactive; pituitary adenomas